Maltose Processing and Not β-Amylase Activity Curtails Hydrolytic Starch Degradation in the CAM Orchid Phalaenopsis - Ceusters, Nathalie; Frans, Mario; Van den Ende, Wim; Ceusters, Johan (Frontiers in Plant Science, 2019)
Crassulacean acid metabolism (CAM) is one of the three photosynthetic pathways in higher plants and is characterized by high water use efficiency. This mainly relies on major nocturnal CO2 fixation sustained by degradation of storage carbohydrate such as starch to provide phosphoenolpyruvate (PEP) and energy. In contrast to C3 plants where starch is mainly degraded by the hydrolytic route, different observations suggested the phosphorolytic route to be a major pathway for starch degradation in CAM plants. To elucidate the interplay and relevant contributions of the phosphorolytic and hydrolytic pathways for starch degradation in CAM, we assessed diel patterns for metabolites and enzymes implicated in both the hydrolytic route (β-amylase, DPE1, DPE2, maltase) and the phosphorolytic route (starch phosphorylase) of starch degradation in the CAM orchid Phalaenopsis “Edessa.” By comparing the catalytic enzyme activities and starch degradation rates, we showed that the phosphorolytic pathway is the major route to accommodate nocturnal starch degradation and that measured activities of starch phosphorylase perfectly matched calculated starch degradation rates in order to avoid premature exhaustion of starch reserves before dawn. The hydrolytic pathway seemed hampered in starch processing not by β-amylase but through insufficient catalytic capacity of both DPE2 and maltase. These considerations were further corroborated by measurements of enzyme activities in the CAM model plant Kalanchoë fedtschenkoi and strongly contradict with the situation in the C3 plant Arabidopsis. The data support the view that the phosphorolytic pathway might be the main route of starch degradation in CAM to provide substrate for PEP with additional hydrolytic starch breakdown to accommodate mainly sucrose synthesis.